A comprehensive study on low-temperature sintering and microwave/terahertz dielectric properties of Bao-P2o5 binary ceramics - Wang, Chang Hao; Zhang, Kai Heng; Wang, Wei; Bao, Jian; Jiang, Jia Pei; Zhou, Ke Hong; Li, Jun; Liang, Chao; Liu, Da Wei; Darwish, Moustafa Adel; Zhou, Tao; Xu, Di Ming; et al. (Royal Society of Chemistry, 2025)
In this study, the sintering characteristics, microstructure, phase composition, crystal structure, dielectric properties, and thermal properties of ceramic samples in the BaO-P2O5 binary system were comprehensively investigated. Furthermore, the intrinsic dielectric properties of ceramic samples in the BaO-P2O5 binary system were elucidated through the analysis of Fourier transform infrared (FTIR) reflectance spectra and terahertz time-domain spectra (THz-TDS). The experimental results showed that BaP2O6 ceramics exhibited good microwave dielectric properties after sintering at 800 °C for 2 h: permittivity (ϵr) = 6.3, quality factor (Q × f) = 17 100 GHz (@12.75 GHz), and τf (TCF, temperature coefficient of resonant frequency) = −45 ppm °C−1. Ba3P2O8 + 2 wt% BCB ceramics exhibited excellent microwave dielectric properties after sintering at 800 °C for 2 h: ϵr = 10.1, Q × f = 75 000 GHz (@11.05 GHz), and τf = +9 ppm °C−1. Moreover, they showed good chemical compatibility with Ag and Cu electrodes. A cylindrical dielectric resonant antenna (DRA) element was designed based on Ba3P2O8 + 2 wt% BCB ceramics, and a 1 × 4 line array was designed based on the unit antenna model. The 1 × 4 DRA line array exhibited a high radiation efficiency of 95%, accompanied by a realized gain of 9.5 dBi. The utilization of Ba3P2O8 + 2 wt% BCB ceramics is anticipated for 5.8 GHz Wi-Fi communication. This study presents a comprehensive theoretical framework and technical guidance for developing ceramics in the BaO-P2O5 binary system.